NFM-12. ENHANCING BRAIN LESIONS IN CHILDREN WITH NEUROFIBROMATOSIS TYPE 1. Issue 2 (22nd June 2018) - Fernandes, Mariana; Passos, João; Garcez, Daniela; Mafra, Manuela; Nunes, Sofia; Salgado, Duarte
Abstract: Children with Neurofibromatosis type 1 (NF1) are at an increased risk of developing glial tumors. Gadolinium enhancement signals blood-brain barrier breakdown and implies tumor activity. In an attempt to determine the prevalence and outcome of enhancing brain lesions in children with NF1, we performed a retrospective analyses of all patients with NF1 followed in a Pediatric Neuro-Oncology department with periodic brain MRI. Of 67 patients whose follow up included neuroimaging studies (optic pathway gliomas 62, other low grade gliomas 3, enhancing lesion 1, T2 hyperintensity 1), 17(25, 3%) showed evidence of enhancing brain lesions (median age at diagnosis 8 years). A total of 25 lesions were identified, mainly in the posterior cranial fossa compartment (60%). Four lesions (4 patients) were symptomatic. One symptomatic patient (mesencephalic lesion), underwent solely a ventriculostomy. Three symptomatic and 3 asymptomatic patients (based on imagiological progression) underwent chemotherapy (complete response obtained in 3 patients, partial response in 2, 1 patient under treatment). In patients who didn't underwent chemotherapy, spontaneous regression was observed in 8 lesions (7 patients), the others remain imagiological stable. Mean follow up time 4, 5 years. In our experience, enhancing brain lesions are prevalent in children with NF1, and although gadolinium enhancement suggests glioma, the proliferative potential remains questionable. The best approach of this lesions is far from being determined. We admit that symptomatic lesions should be treated. In asymptomatic lesions, watchful surveillance may be appropriate and decision to treat must take in consideration multiple aspects, namely imagiological progression.